Deixis Analysis in Maher Zein's Song "For the Rest of My Life" - Hamdani, Danial (Journal of English Language and Pedagogy (JELPA), 2023)
This research analyses the Deixis in Maher Zein's song "For the Rest of My Life" to reveal the layers of meaning embedded within the lyrics. Deixis refers to language elements that indicate specific meaning within a given context. The study employs a descriptive qualitative methodology, focusing on the types of Deixis by Levinson used in the lyrics and the intended meaning conveyed through the song. The analysis identifies five types of Deixis: person, time, place, discourse, and social. The results show that the song predominantly utilizes person, place, and time deixis, emphasizing the singer's emotional connection and lifelong commitment. Additionally, discourse deixis fosters a direct relationship with the listener, while social Deixis underscores the singer's expressions of love and devotion towards specific individuals. In the cultural and religious context, the nuanced analysis reflects Islamic values of introspection, enduring commitment, interpersonal relationships, and love as a source of strength and unity.